Effectiveness of Digital Intervention on Improving Mental Health Literacy and Health Service Utilization - Akmal Hidayat; Nur Aeni Rahman; Zahrotul Ainil Mahfudhah Umar; Nurfaisa Riono; Abd Majid (Program Studi Teknik Komputer, 2025)
The purpose of this study is to assess how well the